Form and Function in Grammar Teaching - J. E. Lisa Meyer (TEFLIN Journal: A publication on the teaching and learning of English, 1998)
Abstract :In this paper we promote the integration of form-focused grammar teaching with a communicative approach to language learnÃÂing. After discussion of several principles of L2 acquisition and their pedagogic implications, we recommend a four-stage lesson plan which helps the teacher to focus on a communicative function while presenting a specific grammatical structure. In the proposed lesson structure, teachers are encouraged to guide student. Exploration, disÃÂcovery, and application of grammatical information during specific lesson stages. This type of lesson should pave the way for students to do more than master practice worksheets. One of the greatest benÃÂefits of this type of lesson is that it gives teachers the confidence to integrate a grammatical focus into their language lessons without violating the essence of communicative approach.